Activation of cannabinoid CB1 receptor contributes to suppression of spinal nociceptive transmission and inhibition of mechanical hypersensitivity by Aβ-fiber stimulation. Issue 11 (November 2016) - Yang, Fei; Xu, Qian; Shu, Bin; Tiwari, Vinod; He, Shao-Qiu; Vera-Portocarrero, Louis P.; Dong, Xinzhong; Linderoth, Bengt; Raja, Srinivasa N.; Wang, Yun; Guan, Yun
Abstract : Abstract: Activation of Aβ-fibers is an intrinsic feature of spinal cord stimulation (SCS) pain therapy. Cannabinoid receptor type 1 (CB1) is important to neuronal plasticity and pain modulation, but its role in SCS-induced pain inhibition remains unclear. In this study, we showed that CB1 receptors are expressed in both excitatory and inhibitory interneurons in substantia gelatinosa (SG). Patch-clamp recording of the evoked excitatory postsynaptic currents (eEPSCs) in mice after spinal nerve ligation (SNL) showed that electrical stimulation of Aβ-fibers (Aβ-ES) using clinical SCS-like parameters (50 Hz, 0.2 millisecond, 10 μA) induced prolonged depression of eEPSCs to C-fiber inputs in SG neurons. Pretreatment with CB1 receptor antagonist AM251 (2 μM) reduced the inhibition of C-eEPSCs by Aβ-ES in both excitatory and inhibitory SG neurons. We further determined the net effect of Aβ-ES on spinal nociceptive transmission in vivo by recording spinal local field potential in SNL rats. Epidural SCS (50 Hz, Aβ-plateau, 5 minutes) attenuated C-fiber-evoked local field potential. This effect of SCS was partially reduced by spinal topical application of AM251 (25 μg, 50 μL), but not CB2 receptor antagonist AM630 (100 μg). Finally, intrathecal pretreatment with AM251 (50 μg, 15 μL) in SNL rats blocked the inhibition of behavioral mechanical hypersensitivity by SCS (50 Hz, 0.2 millisecond; 80% of motor threshold, 60 minutes). Our findings suggest that activation of spinal CB1 receptors may contribute to synaptic depression to high-threshold afferent inputs in SG neurons after Aβ-ES and may be involved in SCS-induced inhibition of spinal nociceptive transmission after nerve injury. Abstract : This study shows for the first time that Aβ-fiber excitation activates spinal CB1 receptors to inhibit spinal nociceptive transmission and mechanical hypersensitivity after nerve injury.